Do preschoolers grasp the importance of regulating emotional expression?. Issue 4 (4th July 2021) - Pala, F. Cansu; Lewis, Charlie
ABSTRACT: A grasp of the fact that emotional displays may not match a person's underlying feelings has been thought to develop in the elementary school years. Two prominent scales address the issue of how one might feel a negative feeling but need to display an different expression. Data from these scales suggest that children's comprehension of the need to regulate emotional expression may emerge as the child starts school. This study aimed to create a more comprehensive analysis of the understanding of regulation of emotions and test a younger cohort. Sixty-two 3-5-year-old children, in Turkish preschools, were presented with nine vignettes depicting scenes in which protagonists are required not to reveal their actual feelings. Participants were required to assess how the protagonist should manage their emotional displays. Performance in the stories was consistent. The 4- and 5-year-olds, but not 3-year-olds, performed better and were above chance in several individual trials in which they needed to attribute a protagonist with a need to regulate their emotional expression while thinking of an unrealized goal. Our findings suggest that children grasp the distinction between socially appropriate emotion displays and what is felt at the age of 4, a time when several other similar developments take place.